Analisis Tingkat Pemahaman Akuntansi Mahasiswa dengan Model Pembelajaran Role-Play (Studi Kasus: Mahasiswa Jurusan Akuntansi Politeknik Negeri Padang) - Diki Supriadi; Josephine Sudiman; Lisa Amelia Herman (Jurnal Pasar Modal dan Bisnis, 2019)
This research was conducted at Padang State Polytechnic Department of Accounting. Students of this department acted as junior accountants in a role-play learning model with the aim to study their level of understanding at preparing basic financial reporting. Research method used is a qualitative descriptive method by conducting interviews, observations and documentation to obtain data and information that is accurate and similar to actual situations. The results showed that participants with a high accounting understanding level as much as 58%, a moderate accounting understanding level as much as 25% and with a low accounting understanding level as much as 17%. The results also show that the obstacles during this role-play learning model are lack of participants’ effort to learn the given modules and to act accordingly.